METODE MENGAJAR GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MELALUI AKTIVITAS BELAJAR - Ajeng Nabila Dini Saputri; Tedi Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2016)
This study aimed to determine whether there is an influence of students' perceptions about the methods of teaching and learning motivation on learning outcomes of the economy through learning activities. This method used descriptive method approach verification ex post facto and surveys. The data collection technique was path analysis. The research showed that, there are significant influence of: 1. Perception of students on teaching methods to the learning activity 2. Motivation towards learning activities 3. Relationship of students' perception on teaching methods and motivation 4. Perceptions of students on teaching methods on learning outcomes 5. Motivation for learning outcomes 6 . Perceptions of students on teaching methods on learning outcomes through learning activities 7. Motivation for learning outcomes through learning activities 8. Cruising on learning outcomes 9. Perceptions of students on teaching methods and motivation toward learning activities 10. students' perceptions about the methods of teaching and learning activities on learning outcomes.Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh persepsi siswa tentang metode mengajar dan motivasi belajar terhadap hasil belajar ekonomi melalui aktivitas belajar. Metode ini menggunakan metode deskriptif verifikatif dengan pendekatan ex post facto dan survey. Teknik pengumpulan data adalah analisis jalur. Hasil penelitian menunjukan, terdapat pengaruh : 1. Persepsi siswa tentang metode mengajar terhadap aktivitas belajar 2. Motivasi terhadap aktivitas belajar 3. Hubungan persepsi siswa tentang metode mengajar dengan motivasi 4. Persepsi siswa tentang metode mengajar terhadap hasil belajar 5. Motivasi terhadap hasil belajar 6. Persepsi siswa tentang metode mengajar terhadap hasil belajar melalui aktivitas belajar 7. Motivasi terhadap hasil belajar melalui aktivitas belajar 8. Aktivitas belajar terhadap hasil belajar 9. Persepsi siswa tentang metode mengajar dan motivasi terhadap aktivitas belajar 10. Persepsi siswa tentang metode mengajar dan aktivitas belajar terhadap hasil belajar.Kata kunci: aktivitas belajar, metode mengajar, motivasi belajar dan hasil belajar.